Section 69(1) Of The Employment Act, 1955: Judicial Misunderstanding Of Legislative Intent - Ahmad, Sharifah Suhana (Journal of Malaysian and Comparative Law, 2019)
As a very wise man once observed, "words are the source of misunderstandings". Whoever invented the saying, "silence is golden" must have experienced the trauma often accompanying the interpretation and understanding of the spoken word.